Anne Bradstreet in her time - Jiménez de Peralta, Susana; Cabrera Bueno, Angélica
Our thesis consists of five chapters. The First Chapter offers a brief summary of the conditions in Bradstreet´s time. The Second Chapter provides an overview of Bradstreet´s life. The Third and Fourth chapters introduce Bradstreet´s poems, a short analysis of some of her poems, Anne´s personality and her legacy. Finally, the Last Chapter is a brief conclusion about whether Bradstreet´s works reflect her time or not. The New World was not just a safe place for the practice of religion; it was also fertile ground for the development of Anne Bradstreet´s poems and writing talent. Anne Bradstreet was more than a wife and mother of eight children. She was the first published American poet, who, through her poetry, subtly challenged stereotypes of Puritans, revealing her vibrant intellectualism and her outspoken love for her husband. Anne Bradstreet lived in England in the colonies during a remarkable historic period marked by civil and religious strife and political disturbance in Europe. The broad scope of her learning and reading is evident in the literary and historical allusions of her early poems. Her later verse and her prose meditations strike a more personal note, revealing both a passionate religious sense and a depth of feeling for her husband, her children, the fears and disappointments she faced, and the consoling power of nature